2001
DOI: 10.1103/physreva.63.052509
|View full text |Cite
|
Sign up to set email alerts
|

Radiative-recoil corrections of orderα(Zα)5(m/M)mto the Lamb shift revisited

Abstract: The results and main steps of an analytic calculation of radiative-recoil corrections of order α(Zα) 5 (m/M )m to the Lamb shift in hydrogen are presented. The calculations are performed in the infrared safe Yennie gauge. The discrepancy between two previous numerical calculations of these corrections existing in the literature is resolved. Our new result eliminates the largest source of the theoretical uncertainty in the magnitude of the deuterium-hydrogen isotope shift.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 10 publications
4
49
0
Order By: Relevance
“…In such a case an exact calculation will produce an extra factor 1/(1 + m/M) before the skeleton integral in eq. (280). We have considered above only the nonrecoil contributions, and so we have ignored an extra factor of order m/M, keeping in mind that it would be considered together with other recoil corrections of order α(Zα)E F .…”
Section: Fig 70 Diagrams With Electron-loop Polarization Insertionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such a case an exact calculation will produce an extra factor 1/(1 + m/M) before the skeleton integral in eq. (280). We have considered above only the nonrecoil contributions, and so we have ignored an extra factor of order m/M, keeping in mind that it would be considered together with other recoil corrections of order α(Zα)E F .…”
Section: Fig 70 Diagrams With Electron-loop Polarization Insertionsmentioning
confidence: 99%
“…Respective contributions once again may be calculated with the help of the skeleton integral in eq. (280) [238,241,242].…”
Section: B Corrections Of Order α 2 (Zα)e Fmentioning
confidence: 99%
See 1 more Smart Citation
“…An insensitive, sterile value is not theoretical, it is rather a mathematical one, and that is the case for the difference ∆(2) and the 2p j energy. Details of theoretical calculations can be found in the review [1]. …”
Section: Hydrogen Lamb Shiftmentioning
confidence: 99%
“…We do not try to review theoretical calculations (if necessary details can be found in Ref. [1]), but present state of art in physics of simple atoms and discuss in detail the theoretical and experimental status of studying such atoms. …”
mentioning
confidence: 99%